A swiftly tilting planet - L'Engle, Madeleine (New York Square Fish/Farrar, Straus and Giroux, 1978)
The youngest of the Murry children must travel through time and space in a battle against an evil dictator who would destroy the entire universe
13
Keywords: Science fiction; Good and evil -- Juvenile fiction; Space and time -- Juvenile fiction; Time travel -- Juvenile fiction